Mineralogical characteristics and applications of iron ore from the mineral province of Carajás: a review (Research, Society and Development, 2022)
Iron ore is essential for obtaining steel, which is a material widely used in our society. In Brazil, the main mineralogical reserves associated with iron deposits are located in the mineral province of Carajás, located in the state of Pará. This study presents, for the ore obtained in the province of Carajás, a review of its general characteristics such as: occurrence, alteration, composition, physical properties and applications. Through literature data it was observed that hematite, magnetite and goethite are present in the iron ore found in the province of Carajás. As exposed, this investigation displays useful information with potential benefit for the mineral and industrial sector.